PROGRAM PELATIHAN UNTUK MENGATASI GEJALA INTRADIALISIS DAN MEMPERCEPAT PEMULIHAN PASCAHEMODIALISIS - Antari, G.A.A.; Devi, N.L.P.S; Widyanthari, D.M.; Manangkot, M.V. (Buletin Udayana Mengabdi, 2024)
Intradialytic symptoms are symptoms or complaints reported by patients during hemodialysis sessions. Generally, more than 85% of patients report experiencing pain like muscle cramps. The presence of intradialytic symptoms can make the patient more tired after hemodialysis and take longer to feel better. As a result, there is a decrease in quality of life and an increased risk of hospitalization. The hemodialysis patient training program is a solution to assist patients in overcoming intradialytic symptoms and accelerating posthemodialysis recovery. The program aims to improve the patient's understanding and ability to cope with intradialytic symptoms and accelerate post-hemodialysis recovery. This program focuses on several aspects, namely increasing patient knowledge, increasing the patient's ability to cope with emerging symptoms, and increasing patient understanding of post-hemodialysis recovery. The implementation method is in the form of providing education and training to overcome intradialytic symptoms. The results showed that there was an increase in the patient's knowledge and ability in symptom management, especially regarding the management of cramps and the patient was able to perform intradialytic exercises. In addition, it was also found that the recovery time after hemodialysis was accelerated and the patient felt more fit. Therefore, training like this is very important to be carried out on an ongoing basis for hemodialysis patients. Keywords: intradialytic symptom, hemodialysis, training program, recovery time